Emergency neuroradiology : a case-based approach - Tang, Yang; Mukherjee, Sugoto; Wintermark, Max (Cambridge : Cambridge University Press, 2015)
Neuroradiological emergencies pose important challenges to the on-call physician, demanding thorough preparedness and quick action. This concise, highly illustrated volume covers all facets of emergency neuroradiology in a clear, easily searchable way, making it ideal both for effective learning and for rapid reference. Over 150 cases, accompanied by nearly 800 high-quality CT and MRI images, guide the reader through both common and uncommon presentations in all three key areas: brain, head and neck, and spine. Each case consists of a short history, images, diagnosis, differential diagnosis, key points in bullet form, and suggested readings. The cases are organized into thematic chapters to provide a structured approach for primary learning, but every case remains independent and fully searchable for guidance when on call. With its practically focused approach, this book is a must for radiology residents, fellows and practicing radiologists, and will also benefit specialists in neurology, neurosurgery and emergency medicine.
Title from publisher's bibliographic system (viewed on 13 May 2016).